Biochemical Properties of Mercuric Reductase from Local Isolate of Bacillus sp for Bioremediation Agent - Purkan Purkan; Yuliana Firdausi Nuzulla; Sofijan Hadi; Endang Triwahyu Prasetyawati (Molekul, 2017)
Mercuric reductase is the important enzyme which catalyzes a reduction of a toxic Hg2+ to non-toxic Hg0. The enzyme which has been potentially used as mercury bioremediation agent is produced by mercury resistant bacteria. These research aims are to determinate the resistance level of a local Bacillus sp to HgCl2 in media, to determine the mercuric reductase activity from the bacteria, and to determine the biochemical properties of the mercuric reductase. The Bacillus sp was grown in the Nutrient Broth media with various of  0; 20; 40; 60; 120; and 160 µM HgCl2 to know the response of the bacteria against mercury, The cell growth of Bacillus sp was measured by optical density (OD) method of at λ 600 nm. The mercuric reductase activity was assayed in the solution of MRA (Mercury Reductase Assay), then the oxidized NADPH was observed by the spectrophotometry method at λ340 nm. The result showed that the Bacillus sp has been resistant to media containing mercury at 120 µM, but the microbial growth was decreased by 50% in media containing mercury 80 µM. The Bacillus sp could produce highly the mercuric reductase enzyme at 16 hours of growth time with enzyme activity as 0.574 Unit/µg. The mercuric reductase from the bacteria has an  optimum activity at pH 6 and temperature 37 °C